Curcumin-based polymer prodrug nanoplatform for high-efficiency immunotherapy by synergistically suppression of head and neck cancer cell stemness - Zhisen Shen; Hao Jiang; Shuaijun Lu; Hailong Tian; Feng Gao; Hongxia Deng; Canhua Huang (Journal of Nanobiotechnology)
Abstract Background Immunotherapy represents a transformative advance in cancer treatment; however, its efficacy in head and neck cancer (HNC) remains constrained by tumor cell stemness and profound immunosuppression within the tumor microenvironment (TME). Overcoming these barriers necessitates innovative strategies to simultaneously eradicate stem-like populations and reprogram the TME. Methods We engineered a tumor-targeted polymer prodrug nanoplatform, Biotin@P-Cur/T780 NPs, integrating disulfide-linked polycurcumin (P-Cur) and the photothermal agent T780. DSPE-PEG-Biotin surface functionalization enables active tumor targeting. The nanoplatform exploits high intratumoral glutathione (GSH) to trigger disassembly, releasing curcumin monomers and T780. This elicits dual GSH depletion and reactive oxygen species (ROS) amplification, inducing ROS-mediated apoptosis and ferroptosis. Concurrently, localized near-infrared irradiation activates T780, synergizing photothermal (PTT) and photodynamic (PDT) therapies to intensify immunogenic cell death (ICD). Results The Biotin@P-Cur/T780 NPs potently suppressed tumor cell stemness in vitro and in vivo. ROS/ferroptosis-driven ICD, amplified by PTT/PDT, reversed TME immunosuppression, enhancing dendritic cell maturation and cytotoxic T lymphocyte infiltration. This multimodal mechanism significantly inhibited primary tumor growth and metastasis in HNC models, while extending survival. Conclusion Our prodrug nanoplatform overcomes key resistance mechanisms in HNC by coordinately targeting stemness, inducing dual apoptosis/ferroptosis, and potentiating ICD through PDT/PTT-enhanced immunomodulation. This strategy provides a potent combinatorial approach to augment immunotherapy efficacy in refractory tumors.